STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI ISLAM MULTIKULTURAL SISWA DI SMP MODERN AL-RIFA’IE - Didit Wing Prasetio; Mohammad Afifulloh; Siti Masruchah (VICRATINA, 2022)
Instilling multicultural Islamic values in students is a program in education that is very important to foster an attitude of tolerance in students so that students are able to appreciate and respect the diversity that exists. The cultivation of multicultural Islamic values provides an understanding to students that being tolerant is not only applied to religious or cultural differences, but also being tolerant in the midst of the diversity of the Muslim community is also very important to implement, this is called Internal Islamic multiculturalism, due to the growth of Community Organizations. that develops among Muslims, it is very important for students to understand Multicultural Islamic Values. The purpose of this study was to find out how the strategy was carried out by PAI teachers in instilling multicultural Islamic values in students at Al-Rifa'ie Modern Junior High School.